A review of intrinsic self-sensing cementitious composites and prospects for their application in transport infrastructures - Abedi, Mohammadmahdi (2021)
Monitoring of transport infrastructures, in terms of early damage detection, can prevent the loss of life and economic damage associated with sudden infrastructure collapse and inform timely intervention, such as repair, to increase the sustainability and service life of infrastructures. Self-sensing cementitious geocomposites with the ability to detect stress, strain, and damage based on a piezoresistive mechanism enable the development of more integrated and viable geomaterial monitoring solutions than existing monitoring technologies. Self-sensing cementitious geocomposites are composed of conductive phases embedded in cementitious geomaterials that exhibit both sensing ability and superior mechanical properties. The states of stress, strain, displacement, and damage in infrastructures can be investigated by analysing the change in their electrical resistance. In this review, different types of self-sensing composites, their preparation, influential parameters, and associated theoretical investigations are discussed in detail to inform future advances in the development of self-sensing geocomposites. The challenges of this technology have also been summarised. This review is expected to stimulate and inform research that explores the development and application prospects of self-sensing cementitious geocomposites.